Vertical adaptation of the center of mass in human running on uneven ground - Ernst, M.; Götze, M.; Müller, R.; Blickhan, R. (Human Movement Science, 2014)
In running we are frequently confronted with different kinds of disturbances. Some require quick reactions and adaptations while others, like moderate changes in ground level, can be compensated passively. Monitoring the kinematics of the runner`s center of mass (CoM) in such situations can reveal what global locomotion control strategies humans use and can help to distinguish between active and passive compensation methods.